Karakterisasi dengan Spektroskopi Infra Merah (FTIR) Serbuk Bonggol Jagung - Maghfiroh, Amalia Ma'rifatul (Universitas Sultan Ageng Tirtayasa, 2023)
Corn cobs contains 40-45% cellulose, 30-35% hemicellulose, and 10-20% lignin, while corn cobs ash contains more than 60% silica with small amounts of metal elements. Silica in corn cob powder can be isolated thermally and nonthermally. Nonthermally silica can be separated with HCl. This research was conducted to isolate silica from corncobs using HCl with variations in calcination temperature and holding time. The silica obtained was then characterized by bonding and its structure using infrared spectroscopy (FTIR). The steps taken were preparing the tools and materials, then preparing the corncob powder, and then preparing silica with HCL and FTIR, as well as data processing and analysis. This study concludes that corncob powder produces silica by isolating it using HCL at 70 ºC for 3 hours and calcining at 800 ºC with a holding time of 4 hours. Based on its FTIR characterization, samples soaked in HCL at 70 ºC resulted in absorption caused by several factors, including single NH, CH, OH, triple bonds, double bonds, and single bonds. This is reinforced by the FTIR results, where the peaks are in regions 1, 2, 3, and 4.